Paediatric Inflammatory Bowel Disease: A Mechanistic Approach to Investigate Exclusive Enteral Nutrition Treatment - Lily Nahidi; Andrew S. Day; Daniel A. Lemberg; Steven T. Leach (Scientifica)
The inflammatory bowel diseases (IBD) include Crohn’s disease (CD) and ulcerative colitis. The disease may present at any age although the peak of presentation is the second and third decades of life. The incidences of these diseases are increasing around the world with the age of presentation getting younger. At present CD is incurable with colectomy being the treatment for severe UC. Although several pharmacological approaches are used to modulate the inflammatory response in IBD, few lead to histological healing and most have side effects. An alternative approach is to use enteral formulae given exclusively (EEN) to treat IBD. EEN requires the consumption of an elemental or polymeric formula, with the exclusion of all other nutrients, for a period of up to 12 weeks. The introduction of EEN as a therapeutic option for IBD was through prudent observation; however, EEN has become an established and reliable option for the treatment of paediatric IBD. Despite this, the mechanisms through which EEN induces disease remission are unknown and remain hypothetical. This review will discuss recent research into EEN both describing clinical features of EEN therapy and discussing the most up-to-date understanding of the mechanisms through which EEN may be reducing intestinal inflammation and inducing disease remission.